Characteristics of Successful International Pharmacy Partnerships - Gina M. Prescott; Lauren Jonkman; Rustin D. Crutchley; Surajit Dey; Lisa T. Hong; Jodie Malhotra; See-Won Seo; Marina Kawaguchi-Suzuki; Hoai-An Truong; Elizabeth Unni; Kayo Tsuchihashi; Nubaira Forkan; et al. (MDPI AG, 2023)
Recommendations for global pharmacy collaborations are predominately derived from US institutions. This study utilized semi-structured interviews of global collaborators to assess important partnership components. Interviewees stated personal connections and understanding of each other's programs/systems were key components. Additionally, collaborators indicate that mutual benefits between partners can exist without the requirement for bidirectional exchange of learning experiences, and request and value partners and learners who are culturally aware, global citizens. This structured interview approach provided key insight into how to develop mutually beneficial, sustainable partnerships and provides additional confirmation that the five pillars of global engagement align with an international audience.